Parentally reported barriers to seeking help and advice for child sleep from healthcare professionals. (5th February 2020) - Cook, Georgia; Appleton, Jane V.; Wiggs, Luci
Abstract: Background: Healthcare professionals (HCPs), largely doctors, paediatricians, health visitors, midwives, and practice nurses, are in a good position to provide information, help, advice, or guidance to parents for child sleep. However, evidence suggests that there is a gap between the number of parents who desire assistance from HCPs and those that make use of these sources, yet very little is known about the reason for this apparent disparity. The aim of this study was to understand the barriers reported by parents to consulting HCPs about child sleep. Methods: In this study, 266 U.K.‐based parents of children aged 6–36 months old completed an online questionnaire (between October 2015 and October 2016) about their help‐seeking behaviours in relation to child sleep. This included reporting perceived barriers to consulting HCPs for child sleep information and advice about problems. Results: Thematic analysis highlighted five themes, which parents reported acted as barriers to them consulting HCPs. Specifically, parents perceived HCPs to have a lack of knowledge or training around the topic of child sleep and that advice would be limited in terms of breadth of information or management options that would be offered. Parents were also concerned about wasting their own or HCPs' time, perceived there was a lack of continuity in the information they received, and held concerns about possible negative consequences for their family if they shared details about any child sleep difficulties. Conclusions: Possible practical approaches to address the barriers reported by parents are highlighted. This includes improving training around the topic of child sleep for HCPs and adapting the content or manner in which the topic of child sleep and any associated issues are addressed with parents.